Traditional beliefs and practices in newborn care among mothers in a tertiary care centre in Dehradun, Uttarakhand, India - Bangari, Akhil; Thapliyal, Sunil Kumar; Ruchi, Ruchi; Aggarwal, Bindu; Sharma, Utkarsh (International Journal Of Community Medicine And Public Health, 2019)
Background: Neonatal care practices are different in different communities. Before any intervention planned to reduce mortality and mortality in community, understanding of local belief and practices is necessary. Some of the harmful practices need to be abandoned and good or harmless practices need to be appreciated. This study was conducted to understand the cultural beliefs and practices in newborn care among residents of Uttarakhand. Methods: This was descriptive, cross-sectional study carried out among 300 postnatal mothers admitted to the hospital. The data was collected using self-administered questionnaires. Statistical analyses of the data was done using SSPS version 22.0. Results: 4% of the mothers believed colostrum to be unsuitable for the newborn. 71% mothers were practicing daily baby massage. 71.3% believed that hot and cold foods can harm their baby’s health. 57.3% practiced application of Kajal on baby’s face. 74.7% of mothers would keep Knife under pillow and 16.7% match box under baby’s cloth. 5.3% mother believed in practice of branding. 81% of mothers accept to practice of pouring oil in baby’s ear. 22.3% mothers believed in isolating mother baby together for 30-40 days. Conclusions: Certain practices are still prevalent like Branding, discarding colostrum, Kajal application, pouring oil in baby’s ear and very restricted dietary regime of mothers. These practices need to be stopped by educating mothers and relatives in postnatal wards.